A study of the comparative anatomy of the lateral compound eyes of arthropods - Glaholm, J (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1947)
In this thesis the interest has centered mainly on the comparative anatomy of the lateral eyes of Arthropods especially the compound eyes, with some particular reference to those of Chilopoda. The comparative anatomy of the eyes of Chilopoda seemed to be of interest, since they possess in most cases simple lateral eyes, which are not characteristic of the adults of any other group of Arthropoda, except Arachnids, to which the Chilopoda are only remotely related In a few cases - in the Scutigeridae - "compound" eyes are present, which are very unusual in their internal anatomy. The following possibilities with regard to the relationships of the Chilopod eyes present themselves. The simple eyes may be the products of degeneration of a compound eye. Alternatively they may be ocelli of a very primitive pre-compound eye type, persisting where in some cases a compound eye has failed to develop. As a third possibility they may have been separately evolved in forms, in which the compound eye was lost or failed to develop. In the last case they would appear to be unrelated to those of any other Arthropods, except possibly those of Diplopods, to which they are very similar in structure. The "compound" eyes may be or the same type as the compound eyes in the remaining Arthropods, with the differences due to degeneration, or to specialisation. Alternatively they may be of a separate type and formed secondarily, either as a single new structure. or a coalescence of ocelli. The enquiry into the interrelationship of these eyes and their relation to the eyes of other Arthropoda raises several points for investigation. For the compound eyes it is necessary to decide whether they were primarily present in the ancestors of some or all of the classes or Arthropods, and whether they have a common or more or less diverse origin with some evolutionary convergence. For the lateral simple eyes it is necessary to decide whether there are any indications in phylogeny, ontogeny or anatomy of the primitive or secondary formation of a compound eye by the aggregation of numerous ocelli or the elaboration of one or these. Such information might be expected to throw light on the origin of the Scutigerid eye. Alternatively any indications of the formation of simple from compound eyes might show whether the Chilopod simple eyes could have evolved in this way from a Scutigerid or some other compound eye. Median eyes are present in some Trilobites, Eurypterida, Crustacea, Hexapods and Arachnida. Although they exhibit considerable variations in structure, they are all clearly simple eyes. As they are absent in Chilopoda and in the remaining Arthropods are entirely separate in origin from the lateral eyes, with a separate seat of innervation, their comparative anatomy is of little interest in this case. The main portion of the thesis deals with the comparative anatomy, origins and relationships of the different types of compound lateral eyes. The second part comprises a short appendix dealing with similar aspects of the lateral ocelli. Detailed descriptions and figures have been given for the eyes of eight species. Some mention is also made of points observed in the internal or external anatomy of species which were studied in less detail. The theoretical conclusions are based on material from the available literature and from these descriptions.
Keywords: Arthropoda -- Anatomy